Association of anxiety symptoms with health care use and costs in people aged 85 and over. (15th March 2019) - Hohls, Johanna Katharina; König, Hans‐Helmut; van den Bussche, Hendrik; Eisele, Marion; Wiese, Birgitt; Oey, Anke; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Stein, Janine; Röhr, Susanne; et al.
Abstract : Objective: To analyze the association of anxiety symptoms with health care use and costs in people aged 85 and older. Methods: Baseline data from AgeQualiDe (N = 856), a multicenter prospective cohort study of primary care patients aged 85 and older, were analyzed. Anxiety symptoms (Geriatric Anxiety Inventory—Short Form) and health care use were assessed via questionnaires. Health care use was monetarily valued using German unit costs to obtain sectoral (inpatient, outpatient, nursing care, medical supplies, and medication) and total costs. Health care use and costs were analyzed in regression models as a function of anxiety symptoms, as well as relevant covariates (predisposing, enabling, and other need characteristics based on the Behavioral Model of Health Care Use). Results: On a descriptive level, people with increased anxiety symptoms (12% of the sample) incurred on average € 10 909 (SD: 16 023) in the last 6 months, 31% more than those without increased anxiety (€ 8303, SD: 11 175; P  = 0.12). Adjusting for predisposing, enabling, and other need characteristics, anxiety symptoms were not significantly associated with health care use or costs. Specifically, need characteristics (morbidity, cognitive decline, and functional impairment) were associated with total or sectoral costs, depending on the cost category analyzed. Conclusion: In a sample of people of the oldest‐old age group, the severity of anxiety symptoms was not associated with health care use or costs, when adjusting for relevant covariates. A longitudinal analysis could assess whether a change in anxiety symptom severity is associated with health care use or costs in old age.